1995
DOI: 10.1111/j.1432-1033.1995.0083f.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Tissue Distribution in Pigs of Tenascin‐X and Tenascin‐C Transcripts

Abstract: -EJB 95 0444/2Tenascin-X and tenascin-C glycoproteins are phylogenetically conserved components of the extracellular matrix, although their specific roles remain to be determined. cDNA probes were produced from pig tenascin-X and tenascin-C genes and were used to examine the tissue distribution of the transcripts in 28 tissues from Large-White pigs, 4.5-42-months old (called adults) and 17 tissues from 87-day-old fetuses. The hybridization of Northern blots with tenascin-X probes revealed, in most tissues, a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 31 publications
2
40
0
Order By: Relevance
“…In developing rats, tenascin-X is expressed in tendon sheaths, ligaments, synovium, muscle, epicardium, and blood vessel adventitia (48), and a similar distribution has also been shown for pigs (49). In mice, tenascin-C and tenascin-X are coexpressed in muscle, gut, skin, and vasculature (50).…”
Section: Tenascin-x Deficiency and Joint Hypermobilitymentioning
confidence: 65%
“…In developing rats, tenascin-X is expressed in tendon sheaths, ligaments, synovium, muscle, epicardium, and blood vessel adventitia (48), and a similar distribution has also been shown for pigs (49). In mice, tenascin-C and tenascin-X are coexpressed in muscle, gut, skin, and vasculature (50).…”
Section: Tenascin-x Deficiency and Joint Hypermobilitymentioning
confidence: 65%
“…The TNXB gene is reported to encode a member of the tenascin family of extracellular matrix proteins that was highly expressed in skin, muscle, tendon sheath, peripheral nerve, and vasculature (Matsumoto et al 1994;Geffrotin et al 1995). Molecular pathogenesis of SLE was considered as the exaggerated B cell response caused by activated T cells or dendritic cells, or soluble mediators such as cytokines (Kyttaris et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Tenascin-X mRNA was highly expressed in some organs (skeletal muscle, lamina propria of the esophagus, extracellular matrices around blood vessels of the kidney and liver) in contrast to that of tenascin-C (smooth muscle, epithelial-mesenchymal interaction) (Matsumoto et al, 1994). The tenascin-C and -X mRNAs also showed different expressions in the embryonic and adult pig organs (Geffrotin et al, 1995). The changes in extracellular matrices were found in the formation of human fibrocartilage (Graham et al, 1996) in which the existence of chondrogenic cell affect the concentration of tenascin (Mackie et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Burch et al (1997) reported observing a 21-hydroylase deficiency, a connective tissue disorder in the skin and joint hyperextensibility associated with the contiguous-gene syndrome involving tenascin-X. Tenascin-X was also mainly observed in tendon, ligaments in adult and testes and skeletal muscle in fetal pigs (Geffrotin et al, 1995). These distributions between tenascin-C and -X play an important role in the formation of mandible between bone matrix and muscle fiber during development.…”
mentioning
confidence: 99%